Unilateral vocal cord palsy as the presentation of metastatic mediastinal adenocarcinoma (Bangladesh Journal of Medical Science, 2018)
Introduction: Unilateral vocal cord palsy is more common than the bilateral cases. The left side is more affected than the right side owing the longer course of the Left recurrent laryngeal nerve. Iatrogenic causes for example thyroidectomy or cardiac surgery predominate the etiology of its incidence.Methods: A review of medical case record.Results: A 68-year-old man presented with voice change for one month duration. It was associated with occasional shortness of breath. Examination showed unilateral Left vocal cord palsy. Further investigation revealed a huge anterior mediastinal mass. A CT-guided biopsy was performed and histopathologically confirmed as adenocarcinoma.Conclusion: Any lesion in the course of recurrent laryngeal nerve can lead to vocal cord palsy and change of voice. A metastatic lesion to mediastinal nodes even though very rare can be one of them. Mediastinal lymphoma is one of its differential diagnoses.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.172-174